Lived experiences of Iranian employed women with maintaining work-life balance: a descriptive phenomenological study - Nastaran Heydarikhayat; Saba Heydarikhayat; Tahmineh Salehian; Narges Heydarikhayat; Camelia Rohani (BMC Women's Health)
Abstract Background Keeping the work-life balance is a situation that can improve employees’ stress levels and well-being. Women need to carefully consider how to balance their career with family life. The aim of this study was to explore the lived experiences of employed women in maintaining work-life balance in 10 centers affiliated with one university of medical sciences. Methods In this descriptive phenomenological study, 16 full-time employed women were selected by purposive sampling. Data collection was done through individualized semi-structured and in-depth interviews with participants. All interviews were analyzed by the seven steps of Colaizzi’s method in MAXQDA version 10. Results Endless work drama with a constant struggle emerged as an overarching theme of the study. Two themes (immersion in home and work challenges), six sub-themes and 30 categories were extracted from data analysis. Subthemes of the study included: A gap in parenting, self-sacrificing, the hidden costs of being employed, intensifying situations, gender shadow, and stuck in organizational issues. Conclusions The participants’ experiences revealed that they were dissatisfied with their situations and faced significant pressures due to career and family challenges in the context of our society. Also, they were often ignored by their employers. These pressures threatened not only the physical and psychological well-being of women, but also the well-being of their families, especially their children. Thus, health policymakers and health managers should plan for development of supportive policies in the healthcare organizations. They can foster a culture of work-life balance for employed women. This can help women be happy and enjoy their work and family lives. Practical implications These results can be beneficial and applied at individual, organizational and societal levels to improve the conditions of employed women. At the individual level, skill development, empowerment, and prioritization of women’s well-being are recommended. At the organizational level, designing flexible human resources policies is advised. Eventually, at the societal level, supportive legislation such as universal maternity leave for all kind of employment, lactation support and anti-discrimination measures are suggested.